PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TIPE JIGSAW UNTUK MENINGKATKAN HASIL BELAJAR PENGANTAR ADMINISTRASI PERKANTORAN PADA SISWA KELAS X DI SMK NEGERI 1 TEMBILAHAN TAHUN AJARAN 2018 - Nofriadi Nofriadi (Universitas Negeri Medan, 2021)
Abstract: Application Of Cooperative Learning Models Jigsaw Type To Improve Learning Outcomes Introduction To Office Administration In Class X StudentsIn Smk Negeri 1 Tembilahan Academic Year 2018. This study aims to improve the learning outcomes of Class X students of Class X SMK Negeri 1Tembilahan in the 2018 academic year. The research subjects were Class X students of SMK Negeri 1 Tembilahan with a total of 36 students. The form of this research is collaborative classroom action research with two cycles as for the problem, namely the low learning outcomes of Introduction to Office Administration due to the lack of variation in learning. The research data shows that student learning outcomes have increased, the value of teacher activity in the first cycle with an average of 68.52%. in the second cycle it increased by an average of 85.93%. Student activity in the first cycle with an average of 64.06%. in the second cycle increased by an average of 89.06%, the research data has increased, where before carrying out the action the jigsaw cooperative learning model at a basic score of 13 people (40%) with an average of 60.05.The first cycle increased with 19 people (65%) completed with an average of 68.08. In the second cycle it increased with 29 people (85%) who completed an average of 76.02%. The increase in overall learning outcomes is 26.59%. Thus it can be concluded that the hypothesis in this study is